Reaching Scalability in Unstructured P2P Networks Using a Divide and Conquer Strategy - Fonseca, Pedro (2009)
Unstructured peer-to-peer networks have a low maintenance cost, high resilience and tolerance to the continuous arrival and departure of nodes. In these networks search is usually performed by flooding, which is highly inefficient. To improve scalability, unstructured overlays evolved to a two-tiered architecture where regular nodes rely on superpeers to locate resources. While this approach takes advantage of node heterogeneity, it makes the overlay less resilient to accidental and malicious faults, and less attractive to users concerned with the consumption of their resources. In this paper we propose a search algorithm, called FASE, which combines a replication policy and a search space division technique to achieve scalability on unstructured overlays with flat topologies. We present simulation results which validate FASE improved scalability and efficiency